Performance Model: Influenced by Human Capital and Job Satisfaction - Santi Riana Dewi; Andari; Nafiuddin; Sukemi (International Journal of Educational and Life Sciences, 2025)
This study aims to determine the factors that affect the company's top performance. The novelty of this study is the construction of human capital, job satisfaction, and performance. The quantitative method is based on a survey approach by distributing questionnaires which are employee perceptions. The number of samples is 99 employees. The software used to analyze the data is SmartPLS. The instrument items in the form of statements that have been filled in will be subjected to validation tests, reliability tests, significance tests, outer loading values, R-square, and bootstrapping. The results of this study show that there is an influence of human capital on performance, and there is an influence of job satisfaction on performance.